The solution of the equation is -6.
The equation rewritten in standard form is:
√(x + 10) - 9 = -7
Add 9 to both sides:
√(x + 10) = 2
Square both sides:
x + 10 = 4
x = -6
Therefore, x = -6 is the solution to the equation.
What is the solution of the equation?
StartRoot x plus 10 EndRoot minus 9 equals negative 7
(1 point)
Responses
–6
–6
4
4
14
14
–8
3 answers
What is the solution of the equation?
4 left parenthesis 3 minus x right parenthesis Superscript StartFraction 4 over 3 EndFraction baseline minus 5 equals 59
(1 point)
Responses
–5, 11
–5, 11
5
5
11
11
–11
4 left parenthesis 3 minus x right parenthesis Superscript StartFraction 4 over 3 EndFraction baseline minus 5 equals 59
(1 point)
Responses
–5, 11
–5, 11
5
5
11
11
–11
To solve the equation:
4(3 - x)^(4/3) - 5 = 59
First, add 5 to both sides:
4(3 - x)^(4/3) = 64
Divide by 4:
(3 - x)^(4/3) = 16
Raise both sides to the power of 3/4:
3 - x = 16^(3/4)
3 - x = 8
Now, subtract 3 from both sides:
-x = 5
Divide by -1 to solve for x:
x = -5
Therefore, x = -5 is the solution to the equation.
4(3 - x)^(4/3) - 5 = 59
First, add 5 to both sides:
4(3 - x)^(4/3) = 64
Divide by 4:
(3 - x)^(4/3) = 16
Raise both sides to the power of 3/4:
3 - x = 16^(3/4)
3 - x = 8
Now, subtract 3 from both sides:
-x = 5
Divide by -1 to solve for x:
x = -5
Therefore, x = -5 is the solution to the equation.